Implementasi Pendekatan Culturally Responsive Teaching untuk Meningkatkan Motivasi Belajar Siswa Materi IPAS - Rahayu, Eka Citra; Ningsih, Puji Rahayu (YASIN, 2025)
This classroom action research was conducted to enhance students' learning motivation in the IPAS (Science and Social Studies Integration) subject using the Culturally Responsive Teaching (CRT) approach. The research was carried out through four main stages: planning, implementation, observation, and reflection, involving 15 fifth-grade A students. Data collection techniques included observation of students' learning activities and a learning motivation questionnaire. The results showed a significant increase in students’ learning motivation, with indicators such as desire and willingness to learn reaching 88.8%, learning drive and needs at 88.3%, appreciation in learning at 86.6%, engagement in interesting activities at 93.3%, and support from the learning environment at 91.6%.Furthermore, the implementation of the Culturally Responsive Teaching (CRT) approach not only improved students’ motivation but also provided a more meaningful learning experience. This approach facilitates the acknowledgment of students’ cultural backgrounds, strengthens their self-confidence in the learning process, and promotes respect and tolerance toward cultural differences in the classroom. Thus, CRT is proven to be an effective approach in creating an inclusive, relevant, and empowering learning environment within the context of 21st-century education.